Let the variables be x and y. The substitution method has
four basic steps:
Now I will apply these steps
to an example, and I will label them so you can understand what
I'm doing at each step.
Step 1: solve eq. 1 for y
x=-2y+1
2y=-x+1
y=(-x+1)/2
Step 2: substitute value of y in eq. 2
x = y - 5
x = ((-x+1)/2) - 5
Step 3: solve step 2's eq. for x
x = -x/2 + 1/2 - 5
(3/2)x = -9/2
3x = -9
x = -3
Step 4: substitute value of x in step 1's eq.
y=(-x+1)/2
y=(-(-3)+1)/2
y=(3+1)/2
y=4/2
y=2
Now you should check your
answers in the original equations.